Structural Characteristics of the Egyptian Clay as a Low-Cost Adsorbent - Shehata, Nabila; El-Geundi, Mohammad S; Ashour, Eman A; Abobeah, Reda M. A (International Journal of Chemical and Process Engineering Research, 2016)
A study of the characteristics of clay from El-Sheikh Fadl Village, El-Minia governorate in Egypt has been carried out. A crucial factor in the applying clay as a low-cost adsorbent, however, is the understanding of the physical, chemical, mineralogical, and colloidal properties of these clays. The characteristics of texture such as surface area, pore volume, porosity, pore size distribution, particle shape and density were determined. The pore size distribution results showed that natural clay is predominantly mesoporous. The thermal behavior of clay was studied using differential thermal analysis and thermogravimetric analysis analysis. The X-Ray diffraction analysis was performed in order to determine the main constituents of the materials. The X-Ray diffraction analysis verified the presence of kaolinite, montmorillonite and quartz in the natural clay. Then clay was tested for infrared spectra, it confirm the presence of the constituents mentioned above. The structure and chemical composition, exchangeable ion type and small crystal size of montmorillonite are responsible for several properties, including a large chemically active surface area.